MENINGKATKAN KEMAMPUAN DAN PEMAHAMAN MEMBACA SISWA DENGAN TEKNIK MEMBACA CEPAT DI SEKOLAH DASAR - Indah Cahyani, Feby; Mursidah Rahmah; Amar Tsani Ulin Nuha; Kintani Diva Shalsabilla; Adhistasya Mahiswara Ary Saputri; Agung Rakhmad Kurniawan; Epon Nurlaela (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The reading ability of grade III students of SD N Julang, Bogor City is still in the low category. This is indicated by the results of the initial test that was carried out that out of a total of 28 students, only 7 students completed the speed reading and only 10 students completed the comprehension test. The low reading ability and comprehension of students is partly due to the lack of application of speed reading techniques in classroom learning. The purpose of this study was to improve the reading ability and comprehension of grade III students of SD N Julang by using speed reading techniques. This study used the PTK method which was carried out in two cycles. The test results showed that there was an increase in students' reading ability and comprehension from cycle 1 to cycle 2. Thus, the use of speed reading and comprehension techniques can improve the ability of speed reading techniques and comprehension of grade III students of SD N Julang, Bogor City.